2015
DOI: 10.1080/00032719.2015.1022824
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Continuum Source Atomic Absorption Spectrometry with Microwave-Assisted Extraction for the Determination of Metals in Vegetable Sprouts

Abstract: The goal of this study was to investigate the enrichment of garden cress (Lepidium sativum), mung beans (Vigna radiata), and soybeans (Glycine max) with minerals. Hydroponic nutrient solutions were enriched with Zn 2þ ,Cr 3þ , Ca 2þ , Mg 2þ , and Se 2þ . Morphological assessment was based on monitoring changes that occurred as a function of the concentrations of elements in the medium. The growth of the plant, as a result of a stimulating or inhibitory effect of the identity and concentration of elements on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…UV-C sterilization had no influence on Fe and Mg concentrations in the tested sprouts. The study by Blicharska et al [ 23 ] reported that there is a slight correlation between the occurrence of microbiological contamination of sprouts and the presence of a particular type of ion in the hydroponic media or tested plant species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…UV-C sterilization had no influence on Fe and Mg concentrations in the tested sprouts. The study by Blicharska et al [ 23 ] reported that there is a slight correlation between the occurrence of microbiological contamination of sprouts and the presence of a particular type of ion in the hydroponic media or tested plant species.…”
Section: Resultsmentioning
confidence: 99%
“…Biofortification is understood as a process that increases the uptake and accumulation of mineral nutrients in agricultural products through the selection of agricultural practices, plant breeding, or/and product modification via genetic engineering [ 14 , 20 , 21 , 22 ]. The results should provide health benefits as well as pose a minimal risk for consumers [ 23 ]. Through biofortification, the nutrient content increases during crop growth rather than during crop processing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atomic absorption spectrometry (AAS), inductively coupled plasma optical emission spectrometry (ICP-OES), and inductively coupled plasma mass spectrometry (ICP-MS) are the most commonly used instru-mental techniques for the determination of the trace level analysis of environmental samples (26)(27)(28)(29)(30)(31). However, a separation-preconcentration step prior to analysis is necessary due to matrix effects since the analyte levels are often lower than the detection limits of the instrument (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%